Control with minimum energy in processes described by the parabolic equation with non-classical boundary conditions for not self-interfaced spectral problem - Гасанов, К.К.; Гасанова, А.Н. (Proceedings of National Aviation University (archive), 2010)
In the paper a problem of control with minimum energy for heat conduction equation with non-classical boundary conditions is investigated.